Prediction of low frequency vibration and sound propagation through reinforced concrete structures - Carreira, A. S. (2014)
Prediction of low frequency sound fields generated in buildings by internal sources as machines or external sources such as road or rail traffic is a difficult task. Assuming that the source is well known, predictions are generally based on the Finite Element Method (FEM), which is used to model building structures and vibration and sound fields, but other hybrid or coupling methods also can be used. In general, these methods are too much time consuming and provide results which are reliable only below 100-150 Hz. Reliability at higher frequencies requires much larger models. It is, thus, important to develop simpler methods to be used with confidence by acousticians and other consultants. In the present paper a method for prediction of vibration propagation to building slabs based on the use of simplified transfer functions between fundamental joints of the structure is presented. The method was developed numerically for traditional multi-storey building with reinforced concrete slabs supported by reinforced concrete beams and columns and also was experimentally validated. The method can be used together with theoretical modal analysis to predict sound fields in dwellings.